Reduced progression of carotid intima media thickness by pictorial presentation of subclinical atherosclerosis 3-year follow-up from VIPVIZA a randomized controlled trial. (14th October 2021) - Nyman, E; Gronlund, C; Vanoli, D; Liv, P; Norberg, M; Bengtsson, A; Wennberg, P; Wester, P; Naslund, U
Abstract: Background: Reduced progression of carotid intima media thickness (cIMT) and atherosclerotic plaque assessed by carotid ultrasound has been reported in pharmacological intervention studies. We have previously provide evidence for improved primary prevention of cardiovascular diseases by pictorial presentation of subclinical atherosclerosis severity based on reduction in traditional risk scores in 1-year follow-up. Purpose: We aimed to investigate if pictorial presentation of subclinical atherosclerosis severity affected cIMT and plaque progression over a 3-year follow-up period in comparison with a routine primary prevention program. Methods: Visualization of asymptomatic atherosclerotic disease for optimum cardiovascular prevention (VIPVIZA) study is a population-based, randomized controlled trial with blinded evaluators (PROBE design). Participants aged 40, 50 and 60 years were enrolled from a prevention program within the routine primary care. Carotid ultrasound examinations were made at baseline and at 3-year follow-up (n: 3154). The ultrasound examinations included standardized measurements of cIMT in the far wall of common carotid artery at predefined angles due to Meijer's arc. Used angles was 240 degrees for left-mean-cIMT and 120 degrees for right-mean-cIMT. Detection of plaque was based on Mannheim consensus and plaque prevalence was evaluated as absent, unilateral or bilateral plaques. Total plaque area (TPA) was a sum of plaque areas and measured off-line form the longitudinal 2D B-mode images. At baseline, the intervention group (n: 1575) and their primary care physicians received a pictorial presentation describing the severity of subclinical atherosclerosis with graphs and colored figures based on measured cIMT and plaque prevalence (Figure 1). The control group with respective physician (n: 1579) did not receive any information about ultrasound results. The bilateral, left and right mean cIMT, plaque prevalence and TPA at 3-year follow-up were compared between groups. Analysis was performed by analysis of covariance and ordinal proportional odds models. Bonferroni correction was applied to account for multiple comparisons, each individual test was performed using α = 0.01. Results: Reduced cIMT progression in the intervention group was found in left-mean-cIMT with an estimated group difference of −0.011 mm (p=0.001). Estimated group difference of right- and bilateral-mean-cIMT were both −0.005 mm (p=0.223 and 0.036, respectively) (Figure 2). No significant difference between groups was found for plaque prevalence or TPA. Conclusion: Intervention by pictorial presentation of subclinical atherosclerotic severity reduced the progression of cIMT in comparison with a traditional cardiovascular preventive program only. This was largely driven by changes in the left carotid artery. Long-term follow-up will be required to elucidate if the intervention will have a protective effect on future risk of cardiovascular events. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Heart Foundation of Northern Sweden, Västerbotten County Council.